CLASSIFICATION OF DNA BARCODES BASED ON IMAGE PROCESSING TECHNIQUES: A STUDY - S. JYOTHI; K. BHARGAVI (International Journal of Pharma and Bio Sciences, 2016)
DNA barcoding is a method of identifying the species in biological scientific community without involving the morphological clues. DNA barcoding is a molecular method and which uses DNA from a standardized region of the genome to identify the species. Barcodes are machine readable and capable of storing digital information. The image processing based barcode reading systems started to gain importance which provide more information than laser barcode readers at a time. In this paper, a few traditional barcode methods, computer vision based decoding techniques, image processing based barcode reading system & methods and its performance issues are discussed. Image processing based barcode recognition systems are expected to increase the performance in barcode reading. Preprocessing, segmentation, edge detection and optimization techniques were used in DNA barcode classification.